Organic viscosity-reducing warm mixing agent for water conservancy project and preparation method of organic viscosity-reducing warm mixing agent
By using a composite particle structure of partially carbonized plant fibers and self-heating iron powder in the warm mixing agent for water conservancy engineering, combined with naphthalene particles or microcrystalline wax and low melting point EVA resin, the self-heating warm mixing agent has low reaction efficiency in the initial stirring stage. The problem of this problem has achieved more efficient thermal reaction and asphalt construction performance.
Patent Information
- Application Number
- CN202411433411.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-07
AI Technical Summary
The existing self-heating warm mixing agent does not have sufficient contact with the air in the initial stirring period, resulting in low self-heating reaction efficiency and insufficient dispersion performance.
Using a composite particle structure composed from the inside to the outside, the core layer contains partially carbonized plant fibers and self-heating iron powder, the intermediate layer contains naphthalene particles or microcrystalline wax, and the outer cladding layer is a low melting point EVA resin, and the carbonization process is and plasma treatment improves the specific surface area and thermal conductivity of particles, and improves mixing uniformity through ultrasonic dispersion.
The efficiency of self-heating reaction and uniformity of heat energy release are improved, the asphalt construction temperature is reduced, and the dispersion and mixing uniformity of particles in asphalt are enhanced.
Smart Images

Figure CN119264682A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of asphalt materials, and in particular relates to an organic viscosity-reducing warm-mix agent for water conservancy projects and a preparation method thereof. Background Art
[0002] Hydraulic warm mix asphalt concrete is widely used in the core wall of the dam of water conservancy projects. There are high requirements for the anti-seepage and low-temperature characteristics of hydraulic warm mix asphalt concrete. Hydraulic warm mix asphalt concrete is mixed with warm mix agent or adopts other technical means to reduce the mixing and rolling temperature of asphalt by more than 20℃ compared with similar hot mix asphalt concrete. It is a general term for asphalt concrete that meets the performance requirements of hot mix asphalt concrete without basically changing the mix ratio and construction process of asphalt concrete.
[0003] In water conservancy projects, organic viscosity-reducing warm mix agents can be used to improve the construction performance of asphalt mixtures, especially when constructed at lower temperatures. This type of additive can reduce the viscosity of asphalt, allowing it to maintain good fluidity and workability at lower temperatures, thereby reducing energy consumption, reducing harmful gas emissions, and improving construction efficiency and quality.
[0004] Chinese invention patent CN111892336B discloses a self-heating warm-mix asphalt patch and its construction method, belonging to the technical field of road materials, the self-heating warm-mix asphalt patch includes the following components by mass fraction: 62-72% aggregate, 20-30% self-heating material, 6-8.5% repair fluid, 0.3-0.5% engineering fiber; the self-heating material includes a substance that releases heat when it meets water, so that the asphalt patch is heated to 100-120°C during mixing. Chinese patent application CN114149747A discloses a self-heating two-component emulsified asphalt coating, including component A and component B, the raw materials of component A include the following components by weight: 30-50 parts of anionic emulsified asphalt, 10-60 parts of emulsion, 0-100 parts of water, 0-30 parts of filler, 0.05-0.5 parts of defoamer, 0.5 parts of film-forming aid, 0.5-1 parts of thickener; component B is a self-heating material.
[0005] The existing self-heating warm mix agent has the following problems: the self-heating material is wrapped inside the asphalt material, so it has insufficient dispersion performance and insufficient contact with the air in the initial stage of mixing, resulting in low self-heating reaction efficiency.
[0006] Therefore, it is necessary to provide an organic viscosity-reducing warm-mix agent for hydraulic engineering that improves the efficiency of the self-heating reaction, thereby solving the problems of the prior art. Summary of the invention
[0007] The technical problem to be solved by the present invention is that the self-heating material is wrapped inside the asphalt material, resulting in insufficient dispersion performance and insufficient contact with air in the initial stage of stirring, resulting in a low self-heating reaction efficiency.
[0008] The technical solution adopted by the present invention to solve the technical problem is: An organic viscosity-reducing warm-mix agent for water conservancy projects, which is composed of a core layer, an intermediate layer and an outer coating layer from the inside to the outside, wherein the inner core layer comprises a mixture of partially carbonized plant fibers and self-heating iron powder, the intermediate layer comprises a viscosity-reducing material, and the outer coating layer comprises an EVA layer; the melting point of the intermediate layer is higher than that of the outer coating layer; the mass ratio of the partially carbonized plant fibers to the self-heating iron powder is 1-2.5:1; the base material of the self-heating iron powder is selected to have a particle size between 50-200 microns, a purity of more than 98wt%, and a specific surface area between 3-4m² / g; and the length of the plant fiber is 2-5mm.
[0009] Specifically, the partially carbonized plant fiber is a core portion of the plant fiber formed by a carbonization reaction, in which at least a portion of the surface is carbonized and a portion of the original plant fiber is retained.
[0010] Specifically, the viscosity reducing material includes aromatic hydrocarbons.
[0011] Specifically, the aromatic hydrocarbon is naphthalene.
[0012] Specifically, the viscosity reducing material includes: naphthalene particles dispersed in a paraffin matrix, and the mass percentage of the naphthalene particles is between 60-70%.
[0013] Specifically, the VA content of the EVA layer is 40wt% and the melting point is 60-70°C.
[0014] A preparation method for manufacturing the organic viscosity-reducing warm-mix agent for water conservancy projects, the method comprising: preparing a core layer, coating an intermediate layer, and coating an outer coating layer.
[0015] The present invention has the following beneficial effects: 1) Partial carbonization of plant fibers can improve the specific surface area and adsorption performance of plant fibers while maintaining the toughening properties of plant fibers. Partial carbonization of plant fibers can improve the specific surface area and adsorption performance of plant fibers. Partial carbonization of plant fibers can improve the specific surface area and adsorption performance of plant fibers. Partial carbonization of plant fibers can serve as a carrier to help the self-heating iron powder to be evenly distributed in the composite particles, thereby improving the uniformity and efficiency of thermal energy release; partially carbonized plant fibers have good thermal conductivity, which helps to quickly transfer the heat generated by the self-heating iron powder and improve the overall thermal efficiency; partially carbonized plant fibers also have a high specific surface area and rich pore structure, which can effectively absorb oxygen and moisture. When mixed with self-heating iron powder, it can provide the self-heating iron powder with the oxygen and moisture required for the reaction, smoothly promote the oxidation reaction with the self-heating iron powder, and improve thermal efficiency.
[0016] 2) The amino (-NH2) bonds on the surface of the self-heating iron powder can increase the surface activity of the iron powder, enhance its ability to bind with oxygen and a small amount of impurity moisture in asphalt, and improve the efficiency of the thermal reaction.
[0017] 3) Since the melting point of the EVA resin in the outer coating layer (60-70°C) is lower than that of the middle layer, the EVA resin will soften and melt first during the warm mixing process. After the EVA resin melts, a liquid film is formed on the surface of the particles, which reduces the friction between the particles and asphalt, and helps to improve the dispersion and mixing uniformity of the particles in the asphalt.
[0018] 4) When the middle layer is microcrystalline wax, the thermal expansion coefficient of microcrystalline wax is 200-400 × 10⁻ 6 / °C, the thermal expansion coefficient of EVA resin is 50-150 × 10⁻ 6 / °C. During the warm mix process, as the temperature rises, the microcrystalline wax layer will expand more significantly than the EVA resin layer. Due to the large thermal expansion coefficient of microcrystalline wax, its volume growth ratio is greater than that of EVA resin. When the EVA resin melts first, the expansion of the microcrystalline wax layer will generate internal pressure on the EVA liquid film, making the EVA liquid film easier to open. After the EVA liquid film is opened, the porous carbonized coconut shell fiber and self-heating iron powder inside are more likely to flow out and contact with the asphalt substrate, thereby improving the efficiency of the thermal reaction during the warm mix process. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to clearly illustrate the technical solution of the present invention, the drawings of specific implementation methods are briefly introduced below.
[0020] Figure 1 The present invention provides a flow chart of a method for preparing an organic viscosity-reducing warm-mix agent for water conservancy projects. DETAILED DESCRIPTION
[0021] The specific embodiments of the present invention are described in detail below.
[0022] The "range" disclosed in the present invention is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 10 to 50 is listed for a specific parameter, it is understood that the range of 10 to 40 and 20 to 50 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In this application, unless otherwise specified, the range of values "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the range of values "0 to 5" means that all real numbers between "0 to 5" have been fully listed in this article, and "0 to 5" is only an abbreviation of these numerical combinations.
[0023] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0024] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0025] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0026] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0027] Unless otherwise specified, the reaction is carried out at room temperature and pressure.
[0028] Unless otherwise specified, all parts or percentages are by weight.
[0029] In the present invention, all substances used are known substances and can be purchased or synthesized by known methods.
[0030] In the present invention, the devices or equipment used are all conventional devices or equipment known in the art and are commercially available.
[0031] Example 1 The present invention firstly provides an organic viscosity-reducing warm-mix agent for water conservancy projects. The warm-mix agent is a composite particle, which comprises, from the inside to the outside, a core layer, an intermediate layer and an outer coating layer.
[0032] The core layer includes: a mixture of partially carbonized plant fibers and self-heating iron powder, and the mass ratio of the partially carbonized plant fibers to the self-heating iron powder is 1-2.5:1. The partially carbonized plant fibers are common plant fibers used in water conservancy projects, preferably coconut shell fibers. The length of the plant fibers is 2-5 mm. The partially carbonized plant fibers are formed by a carbonization reaction of the plant fibers, at least part of the surface of which is carbonized and part of the original plant fibers are retained.
[0033] Partial carbonization of plant fibers can improve the specific surface area and adsorption performance of plant fibers while maintaining the toughening properties of plant fibers. Partial carbonization of plant fibers can improve the specific surface area and adsorption performance of plant fibers. Partial carbonization of plant fibers can improve the specific surface area and adsorption performance of plant fibers. Partial carbonization of plant fibers can serve as a carrier to help the self-heating iron powder to be evenly distributed in the composite particles, thereby improving the uniformity and efficiency of thermal energy release; partially carbonized plant fibers have good thermal conductivity, which helps to quickly transfer the heat generated by the self-heating iron powder and improve the overall thermal efficiency; partially carbonized plant fibers also have a high specific surface area and rich pore structure, which can effectively absorb oxygen and moisture. When mixed with self-heating iron powder, they can provide the self-heating iron powder with the oxygen and moisture required for the reaction, smoothly promote the oxidation reaction with the self-heating iron powder, and improve thermal efficiency.
[0034] The partial carbonization process of plant fiber is as follows: oven-dry the plant fiber with a length of 2-5 mm to remove excess moisture and dry it at 60-80°C for 2 hours. Pre-oxidation: In order to improve the structural stability during the carbonization process, pre-oxidation treatment is carried out under the protection of inert gas (such as nitrogen). The pre-oxidation temperature is generally 200-300°C and the time is 1 hour. The pre-treated coconut shell fiber is placed in a high-temperature furnace for carbonization. The specific carbonization process is as follows: first, under the protection of inert gas (such as nitrogen or argon), gradually heat up to 400°C for carbonization, and the heating rate is 5-10°C / min. Keep warm at the target temperature for 0.5-1 hour to ensure partial carbonization and maintain the uncarbonized core. After carbonization is completed, turn off the heating source and cool naturally to room temperature under the protection of inert gas.
[0035] If the carbonization temperature is too high or the time is too long, the fiber will be completely carbonized, thereby reducing the mechanical properties of the subsequent asphalt. If the carbonization temperature is too low or the carbonization time is too short, the carbonization will be insufficient and the effect of transferring oxygen and moisture to the self-heating iron powder will not be achieved.
[0036] As a preferred embodiment, after completing the partial carbonization process, a physical activation process of the plant fiber can also be performed, that is, after the carbonization is completed, the carbonized plant fiber is exposed to water vapor, activated for 1 hour, and then dried and cooled, thereby further increasing the porosity.
[0037] The self-heating iron powder is a pure iron powder substrate with a particle size between 50-200 microns, a purity of more than 98wt%, and a specific surface area between 3-4m² / g. The particle size will affect the reaction rate and heat release efficiency of the iron powder. Too large a particle size will reduce the self-heating reaction rate, and too small a particle size may cause agglomeration problems. The pure iron powder substrate is treated with NH3 plasma, and amino (-NH2) bonds are formed on the surface of the iron powder substrate through plasma treatment to obtain self-heating iron powder. The amino (-NH2) bonds on the surface of the self-heating iron powder can increase the surface activity of the iron powder, enhance its ability to bind with oxygen and a small amount of impurity moisture in asphalt, and improve the efficiency of the thermal reaction. The ammonia plasma treatment process is as follows: the iron powder substrate is evenly placed in the plasma treatment chamber, the reaction chamber is evacuated to a vacuum degree between 5 mTorr and 50 mTorr, oxygen and other impurities in the air are removed, high-purity ammonia is introduced into the reaction chamber, and the pressure is adjusted to 5 mTorr to 100 mTorr, and the reaction gas NH3 is introduced, wherein NH3 (reaction gas): N2 (carrier gas) = 10sccm: 300-500sccm, the iron powder substrate is exposed to the ammonia plasma, and the plasma supply rate is controlled at 50-100W. The active nitrogen atoms and hydrogen atoms in the plasma will react with the surface of the iron powder to form amino (-NH2) bonds. By controlling the flow ratio of ammonia (NH3) and nitrogen (N2): NH3 (reaction gas): N2 (carrier gas) = 10sccm: 300-500sccm, the number and distribution of amino (-NH2) bonds formed on the surface of the self-heating iron powder can be effectively controlled, thereby avoiding the slow reaction caused by excessive nitridation and the low NH2 bond content that cannot improve the activity of the iron powder.
[0038] As a preferred embodiment, the outer side of the self-heating iron powder may also include an EVA coating, wherein the VA (vinyl acetate) content in the EVA (ethylene-vinyl acetate copolymer) resin is 40%. Toluene is used as a solvent, and 50g of EVA resin is dissolved in every 1L of toluene to obtain an EVA solution. Use a spray gun to evenly spray the EVA solution on the surface of the self-heating iron powder. Control the spraying speed and distance to ensure that the coating evenly covers the surface of the iron powder, and the spraying thickness is 50 microns to 200 microns. And dry it. Put the iron powder sprayed with the EVA coating after drying into an ultrasonic cleaner, and use the high-frequency vibration of ultrasound to disperse the iron powder. The ultrasonic treatment time is 5-30 minutes.
[0039] The partially carbonized plant fiber and self-heating iron powder in the core layer are mixed in proportion, and a methyl cellulose solution binder (concentration 1wt%-3wt%) of 5%-10% of the total material mass percentage is added to mix, and a high-speed stirrer is used to stir at room temperature for 10 minutes to ensure that the methyl cellulose solution is evenly distributed in the mixture. The mixed material is sent to a granulator and formed into 3-5mm particles by extrusion or roller granulation technology. The temperature is controlled at 60-80°C during the granulation process, and the protective gas is nitrogen.
[0040] The middle layer is directly coated on the outer layer of the core layer. The function of the middle layer is to reduce the mixing temperature of the asphalt, that is, the viscosity reducing material.
[0041] The material of the middle layer can be aromatic hydrocarbons. The aromatic hydrocarbon is naphthalene. In order to facilitate the retention of naphthalene, naphthalene particles can be dispersed in a paraffin matrix, and the mass percentage of naphthalene particles in the mixture is between 60-70%. The paraffin is melted at 50 degrees Celsius, and naphthalene particles (60-70wt%) are added, and stirred quickly. The mixed core layer particles are placed in a rotating container, and the molten viscosity-reducing material is evenly impregnated into the internal mixture using an impregnation method to ensure that each core layer particle is evenly wrapped with a layer of viscosity-reducing material. The rotating container rotates at a speed of 60 rpm for 5 minutes to ensure that the coating is evenly distributed. The impregnated particles are cooled by cold wind to solidify the middle layer. The particles are dispersed using high-frequency vibration of ultrasound, and the ultrasonic treatment time is 5 minutes.
[0042] In addition, the viscosity reducing material can also be wax, preferably a commercially available microcrystalline wax product. The thickness of the wax layer is controlled at 1-2 mm. The microcrystalline wax is heated to above its melting point (80°C) to completely melt it. The mixed core layer particles are placed in a rotating container, and the molten wax is evenly impregnated into the internal mixture using an immersion method to ensure that each core layer particle is evenly coated with a layer of wax. The rotating container rotates at a speed of 150 rpm for 5 minutes to ensure that the coating is evenly distributed. The wax-coated particles are naturally cooled at room temperature, or cooled quickly with cold air to solidify the wax middle layer. The particles are dispersed using high-frequency vibrations of ultrasound, and the ultrasonic treatment time is 5 minutes.
[0043] The outer side of the middle layer includes an outer coating layer, and the outer layer material includes: EVA coating, wherein the VA content in the EVA resin is 40wt% and the melting point is 60-70°C. The thickness of the EVA coating is controlled at 0.5-0.8mm (too large a thickness is not conducive to the outflow of the internal material, and too small a thickness is not conducive to the sealing performance of the material). The EVA is heated to above its melting point (70°C) to make it completely melted. Use a spray gun to evenly spray the EVA melt on the surface of the particles. Control the spraying speed and distance to ensure that the coating evenly covers the surface of the iron powder, and the spraying thickness is 500 microns to 800 microns. And dry it. Use the high-frequency vibration of ultrasound to disperse the particles, and the ultrasonic treatment time is 10 minutes.
[0044] Choosing EVA resin with 40% VA content for the outer coating layer also has the following advantages: 1. Since the melting point of EVA resin (60-70°C) is lower than that of naphthalene (80-84°C) and microcrystalline wax (75-85°C), during the warm mixing process, EVA resin will soften and melt first. After the EVA resin melts, a liquid film is formed on the surface of the particles, which reduces the friction between the particles and asphalt, and helps to improve the dispersion and mixing uniformity of the particles in the asphalt.
[0045] 2. When wax is selected as the viscosity reducing material, the thermal expansion coefficient of microcrystalline wax is 200-400 × 10⁻ 6 / °C, the thermal expansion coefficient of EVA resin is 50-150 × 10⁻ 6 / °C. During the warm mix process, as the temperature rises, the microcrystalline wax layer will expand more significantly than the EVA resin layer. Due to the large thermal expansion coefficient of microcrystalline wax, its volume growth ratio is greater than that of EVA resin. When the EVA resin melts first, the expansion of the microcrystalline wax layer will generate internal pressure on the EVA liquid film, making the EVA liquid film easier to open. After the EVA liquid film is opened, the porous carbonized coconut shell fiber and self-heating iron powder inside are more likely to flow out and contact with the asphalt substrate, thereby improving the efficiency of the thermal reaction during the warm mix process.
[0046] Example 2 Based on the above organic viscosity-reducing warm-mix agent for water conservancy projects, the present application also provides a method for preparing an organic viscosity-reducing warm-mix agent for water conservancy projects, wherein the viscosity-reducing material includes aromatic hydrocarbons, such as Figure 1 As shown, the method specifically includes: Step 1: preparing a core layer, specifically comprising: 1.1 Partial carbonization process of plant fibers: The plant fibers with a length of 2-5 mm were oven dried to remove excess moisture at 60-80 °C for 2 h.
[0047] Pre-oxidation: In order to improve the structural stability during the carbonization process, pre-oxidation treatment is carried out under the protection of inert gas (such as nitrogen). The pre-oxidation temperature is generally 200-300°C and the time is 1 hour.
[0048] The pretreated coconut shell fiber is placed in a high-temperature furnace for carbonization. The specific carbonization process is as follows: first, under the protection of an inert gas (such as nitrogen or argon), the temperature is gradually raised to 400°C for carbonization, with a heating rate of 5-10°C / min. The temperature is kept at the target temperature for 0.5-1 hour to ensure partial carbonization and maintain the uncarbonized core. After carbonization is completed, the heating source is turned off and the fiber is naturally cooled to room temperature under the protection of an inert gas.
[0049] If the carbonization temperature is too high or the time is too long, the fiber will be completely carbonized, thereby reducing the mechanical properties of the subsequent asphalt. If the carbonization temperature is too low or the carbonization time is too short, the carbonization will be insufficient and the effect of transferring oxygen and moisture to the self-heating iron powder will not be achieved.
[0050] 1.2 Preparation process of self-heating iron powder: Self-heating iron powder is made of pure iron powder with a particle size between 50-200 microns, a purity of more than 98wt%, and a specific surface area of 3-4m² / g. The particle size will affect the reaction rate and heat release efficiency of the iron powder. Too large a particle size will reduce the self-heating reaction rate, and too small a particle size may cause agglomeration problems.
[0051] The pure iron powder substrate is treated with NH3 plasma, and amino (-NH2) bonds are formed on the surface of the iron powder substrate through plasma treatment, thereby obtaining self-heating iron powder. The amino (-NH2) bonds on the surface of the self-heating iron powder can improve the surface activity of the iron powder, enhance its ability to bind with oxygen and a small amount of impurity moisture in asphalt, and improve the efficiency of the thermal reaction. The ammonia plasma treatment process is as follows: the iron powder substrate is evenly placed in the plasma treatment chamber, the reaction chamber is evacuated to a vacuum degree between 5 mTorr and 50 mTorr, oxygen and other impurities in the air are removed, high-purity ammonia is introduced into the reaction chamber, and the pressure is adjusted to 5 mTorr to 100 mTorr, and the reaction gas NH3 is introduced, wherein NH3 (reaction gas): N2 (carrier gas) = 10sccm: 300-500sccm, the iron powder substrate is exposed to the ammonia plasma, and the plasma supply rate is controlled at 50-100W. The active nitrogen atoms and hydrogen atoms in the plasma will react with the surface of the iron powder to form amino (-NH2) bonds. By controlling the flow ratio of ammonia (NH3) and nitrogen (N2): NH3 (reaction gas): N2 (carrier gas) = 10sccm: 300-500sccm, the number and distribution of amino (-NH2) bonds formed on the surface of the self-heating iron powder can be effectively controlled, thereby avoiding the slow reaction caused by excessive nitridation and the low NH2 bond content that cannot improve the activity of the iron powder.
[0052] 1.3 Core layer granulation The partially carbonized plant fiber and the self-heating iron powder in the core layer are mixed in proportion, and the mass ratio of the partially carbonized plant fiber and the self-heating iron powder is 1~2.5:1. Add a methyl cellulose solution binder (concentration 1wt%-3wt%) with a mass percentage of 5%-10% of the total material, mix, and use a high-speed stirrer to stir at room temperature for 10 minutes to ensure that the methyl cellulose solution is evenly distributed in the mixture. The mixed material is fed into a granulator and formed into 3-5mm particles by extrusion or roller granulation technology. The temperature is controlled at 60-80°C during the granulation process, and the protective gas is nitrogen.
[0053] Step 2: Wrap the middle layer Heat the paraffin to above its melting point (50°C) to completely melt it. Add naphthalene particles, where the naphthalene particles account for 60-70% of the total mass percentage of the mixture. If necessary, add an appropriate amount of dispersant. Ultrasonic vibration and stirring for 20 minutes are performed to fully mix the naphthalene particles in the melt. Place the mixed core layer particles in a rotating container, and use the impregnation method to evenly impregnate the molten viscosity-reducing material onto the core layer particles to ensure that each core layer particle is evenly coated with a layer of viscosity-reducing material. The rotating container rotates at a speed of 60 rpm for 5 minutes to ensure that the coating is evenly distributed. The impregnated particles are cooled by cold air to solidify the intermediate layer. The high-frequency vibration of ultrasound is used to disperse the particles, and the ultrasonic treatment time is 5 minutes.
[0054] Step 3: Coating the outer covering layer Select EVA resin with a VA content of 40wt% and a melting point of 60-70°C as the molten raw material. Heat EVA to above its melting point (70°C) to make it completely melted. Use a spray gun to evenly spray the EVA melt on the surface of the particles. Control the spraying speed and distance to ensure that the coating evenly covers the surface of the iron powder, and the spraying thickness is 500 microns to 800 microns. And dry it. Use high-frequency vibration of ultrasound to disperse the particles, and the ultrasonic treatment time is 10 minutes.
[0055] Example 3 Based on the above-mentioned organic viscosity-reducing warm-mix agent for water conservancy projects, the present application also provides a method for preparing an organic viscosity-reducing warm-mix agent for water conservancy projects, such as Figure 1 As shown, the viscosity reducing material includes wax, and the method specifically includes: Step 1: preparing a core layer, specifically comprising: 1.1 Partial carbonization process of plant fibers: The plant fibers with a length of 2-5 mm were oven dried to remove excess moisture at 60-80 °C for 2 h.
[0056] Pre-oxidation: In order to improve the structural stability during the carbonization process, pre-oxidation treatment is carried out under the protection of inert gas (such as nitrogen). The pre-oxidation temperature is generally 200-300°C and the time is 1 hour.
[0057] The pretreated coconut shell fiber is placed in a high-temperature furnace for carbonization. The specific carbonization process is as follows: first, under the protection of an inert gas (such as nitrogen or argon), the temperature is gradually raised to 400°C for carbonization, with a heating rate of 5-10°C / min. The temperature is kept at the target temperature for 0.5-1 hour to ensure partial carbonization and maintain the uncarbonized core. After carbonization is completed, the heating source is turned off and the fiber is naturally cooled to room temperature under the protection of an inert gas.
[0058] If the carbonization temperature is too high or the time is too long, the fiber will be completely carbonized, thereby reducing the mechanical properties of the subsequent asphalt. If the carbonization temperature is too low or the carbonization time is too short, the carbonization will be insufficient and the effect of transferring oxygen and moisture to the self-heating iron powder will not be achieved.
[0059] 1.2 Preparation process of self-heating iron powder: Self-heating iron powder is made of pure iron powder with a particle size between 50-200 microns, a purity of more than 98wt%, and a specific surface area of 3-4m² / g. The particle size will affect the reaction rate and heat release efficiency of the iron powder. Too large a particle size will reduce the self-heating reaction rate, and too small a particle size may cause agglomeration problems.
[0060] The pure iron powder substrate is treated with NH3 plasma, and amino (-NH2) bonds are formed on the surface of the iron powder substrate through plasma treatment, thereby obtaining self-heating iron powder. The amino (-NH2) bonds on the surface of the self-heating iron powder can improve the surface activity of the iron powder, enhance its ability to bind with oxygen and a small amount of impurity moisture in asphalt, and improve the efficiency of the thermal reaction. The ammonia plasma treatment process is as follows: the iron powder substrate is evenly placed in the plasma treatment chamber, the reaction chamber is evacuated to a vacuum degree between 5 mTorr and 50 mTorr, oxygen and other impurities in the air are removed, high-purity ammonia is introduced into the reaction chamber, and the pressure is adjusted to 5 mTorr to 100 mTorr, and the reaction gas NH3 is introduced, wherein NH3 (reaction gas): N2 (carrier gas) = 10sccm: 300-500sccm, the iron powder substrate is exposed to the ammonia plasma, and the plasma supply rate is controlled at 50-100W. The active nitrogen atoms and hydrogen atoms in the plasma will react with the surface of the iron powder to form amino (-NH2) bonds. By controlling the flow ratio of ammonia (NH3) and nitrogen (N2): NH3 (reaction gas): N2 (carrier gas) = 10sccm: 300-500sccm, the number and distribution of amino (-NH2) bonds formed on the surface of the self-heating iron powder can be effectively controlled, thereby avoiding the slow reaction caused by excessive nitridation and the low NH2 bond content that cannot improve the activity of the iron powder.
[0061] 1.3 Core layer granulation The partially carbonized plant fiber and the self-heating iron powder in the core layer are mixed in proportion, and the mass ratio of the partially carbonized plant fiber and the self-heating iron powder is 1~2.5:1. Add a methyl cellulose solution binder (concentration 1wt%-3wt%) with a mass percentage of 5%-10% of the total material, mix, and use a high-speed stirrer to stir at room temperature for 10 minutes to ensure that the methyl cellulose solution is evenly distributed in the mixture. The mixed material is fed into a granulator and formed into 3-5mm particles by extrusion or roller granulation technology. The temperature is controlled at 60-80°C during the granulation process, and the protective gas is nitrogen.
[0062] Step 2: Wrap the middle layer Heat the microcrystalline wax to above its melting point (80°C) to completely melt it. Place the mixed core layer particles in a rotating container and use the dipping method to evenly dip the molten wax into the internal mixture, ensuring that each core layer particle is evenly coated with a layer of wax. Rotate the rotating container at a speed of 150 rpm for 5 minutes to ensure that the coating is evenly distributed. Cool the wax-coated particles naturally at room temperature or use cold air to accelerate cooling to solidify the wax middle layer. Use high-frequency vibration of ultrasound to disperse the particles, and the ultrasonic treatment time is 5 minutes.
[0063] Step 3: Coating the outer covering layer Select EVA resin with a VA content of 40wt% and a melting point of 60-70°C as the molten raw material. Heat EVA to above its melting point (70°C) to make it completely melted. Use a spray gun to evenly spray the EVA melt on the surface of the particles. Control the spraying speed and distance to ensure that the coating evenly covers the surface of the iron powder, and the spraying thickness is 500 microns to 800 microns. And dry it. Use high-frequency vibration of ultrasound to disperse the particles, and the ultrasonic treatment time is 10 minutes.
[0064] Example 4 Based on the above-mentioned organic viscosity-reducing warm mix agent for water conservancy projects, the present application also provides a preferred method for preparing an organic viscosity-reducing warm mix agent for water conservancy projects. This method adds an activation process after partial carbonization on the basis of the preparation method of Example 3, thereby further improving the adsorption capacity of the partially carbonized plant fiber, and further improving the efficiency of transporting the oxidation reaction raw materials to the self-heating iron powder.
[0065] The method specifically includes: Step 1: preparing a core layer, specifically comprising: 1.1 Partial carbonization process of plant fibers: The plant fibers with a length of 2-5 mm were oven dried to remove excess moisture at 60-80 °C for 2 h.
[0066] Pre-oxidation: In order to improve the structural stability during the carbonization process, pre-oxidation treatment is carried out under the protection of inert gas (such as nitrogen). The pre-oxidation temperature is generally 200-300°C and the time is 1 hour.
[0067] The pretreated coconut shell fiber is placed in a high-temperature furnace for carbonization. The specific carbonization process is as follows: first, under the protection of an inert gas (such as nitrogen or argon), the temperature is gradually raised to 400°C for carbonization, with a heating rate of 5-10°C / min. The temperature is kept at the target temperature for 0.5-1 hour to ensure partial carbonization and maintain the uncarbonized core. After carbonization is completed, the heating source is turned off and the fiber is naturally cooled to room temperature under the protection of an inert gas.
[0068] If the carbonization temperature is too high or the time is too long, the fiber will be completely carbonized, thereby reducing the mechanical properties of the subsequent asphalt. If the carbonization temperature is too low or the carbonization time is too short, the carbonization will be insufficient and the effect of transferring oxygen and moisture to the self-heating iron powder will not be achieved.
[0069] After completing the partial carbonization process, the plant fiber is further subjected to a physical activation process, that is, after the carbonization is completed, the carbonized plant fiber is exposed to water vapor, activated for 1 hour, and then dried and cooled, thereby further increasing the porosity.
[0070] 1.2 Preparation process of self-heating iron powder: Self-heating iron powder is made of pure iron powder with a particle size between 50-200 microns, a purity of more than 98wt%, and a specific surface area of 3-4m² / g. The particle size will affect the reaction rate and heat release efficiency of the iron powder. Too large a particle size will reduce the self-heating reaction rate, and too small a particle size may cause agglomeration problems.
[0071] The pure iron powder substrate is treated with NH3 plasma, and amino (-NH2) bonds are formed on the surface of the iron powder substrate through plasma treatment, thereby obtaining self-heating iron powder. The amino (-NH2) bonds on the surface of the self-heating iron powder can improve the surface activity of the iron powder, enhance its ability to bind with oxygen and a small amount of impurity moisture in asphalt, and improve the efficiency of the thermal reaction. The ammonia plasma treatment process is as follows: the iron powder substrate is evenly placed in the plasma treatment chamber, the reaction chamber is evacuated to a vacuum degree between 5 mTorr and 50 mTorr, oxygen and other impurities in the air are removed, high-purity ammonia is introduced into the reaction chamber, and the pressure is adjusted to 5 mTorr to 100 mTorr, and the reaction gas NH3 is introduced, wherein NH3 (reaction gas): N2 (carrier gas) = 10sccm: 300-500sccm, the iron powder substrate is exposed to the ammonia plasma, and the plasma supply rate is controlled at 50-100W. The active nitrogen atoms and hydrogen atoms in the plasma will react with the surface of the iron powder to form amino (-NH2) bonds. By controlling the flow ratio of ammonia (NH3) and nitrogen (N2): NH3 (reaction gas): N2 (carrier gas) = 10sccm: 300-500sccm, the number and distribution of amino (-NH2) bonds formed on the surface of the self-heating iron powder can be effectively controlled, thereby avoiding the slow reaction caused by excessive nitridation and the low NH2 bond content that cannot improve the activity of the iron powder.
[0072] 1.3 Core layer granulation The partially carbonized plant fiber and the self-heating iron powder in the core layer are mixed in proportion, and the mass ratio of the partially carbonized plant fiber and the self-heating iron powder is 1~2.5:1. Add a methyl cellulose solution binder (concentration 1wt%-3wt%) with a mass percentage of 5%-10% of the total material, mix, and use a high-speed stirrer to stir at room temperature for 10 minutes to ensure that the methyl cellulose solution is evenly distributed in the mixture. The mixed material is fed into a granulator and formed into 3-5mm particles by extrusion or roller granulation technology. The temperature is controlled at 60-80°C during the granulation process, and the protective gas is nitrogen.
[0073] Step 2: Wrap the middle layer Heat the microcrystalline wax to above its melting point (80°C) to completely melt it. Place the mixed core layer particles in a rotating container and use the dipping method to evenly dip the molten wax into the internal mixture, ensuring that each core layer particle is evenly coated with a layer of wax. Rotate the rotating container at a speed of 150 rpm for 5 minutes to ensure that the coating is evenly distributed. Cool the wax-coated particles naturally at room temperature or use cold air to accelerate cooling to solidify the wax middle layer. Use high-frequency vibration of ultrasound to disperse the particles, and the ultrasonic treatment time is 5 minutes.
[0074] Step 3: Coating the outer covering layer Select EVA resin with a VA content of 40wt% and a melting point of 60-70°C as the molten raw material. Heat EVA to above its melting point (70°C) to make it completely melted. Use a spray gun to evenly spray the EVA melt on the surface of the particles. Control the spraying speed and distance to ensure that the coating evenly covers the surface of the iron powder, and the spraying thickness is 500 microns to 800 microns. And dry it. Use high-frequency vibration of ultrasound to disperse the particles, and the ultrasonic treatment time is 10 minutes.
[0075] Example 5 Based on the above-mentioned organic viscosity-reducing warm mix agent for water conservancy projects, the present application also provides a method for preparing an organic viscosity-reducing warm mix agent for water conservancy projects. On the basis of Example 3, this method adds an EVA protective layer to the outer layer of the self-heating iron powder, thereby improving the stability of the warm mix agent.
[0076] The method specifically includes: Step 1: preparing a core layer, specifically comprising: 1.1 Partial carbonization process of plant fibers: The plant fibers with a length of 2-5 mm were oven dried to remove excess moisture at 60-80 °C for 2 h.
[0077] Pre-oxidation: In order to improve the structural stability during the carbonization process, pre-oxidation treatment is carried out under the protection of inert gas (such as nitrogen). The pre-oxidation temperature is generally 200-300°C and the time is 1 hour.
[0078] The pretreated coconut shell fiber is placed in a high-temperature furnace for carbonization. The specific carbonization process is as follows: first, under the protection of an inert gas (such as nitrogen or argon), the temperature is gradually raised to 400°C for carbonization, with a heating rate of 5-10°C / min. The temperature is kept at the target temperature for 0.5-1 hour to ensure partial carbonization and maintain the uncarbonized core. After carbonization is completed, the heating source is turned off and the fiber is naturally cooled to room temperature under the protection of an inert gas.
[0079] If the carbonization temperature is too high or the time is too long, the fiber will be completely carbonized, thereby reducing the mechanical properties of the subsequent asphalt. If the carbonization temperature is too low or the carbonization time is too short, the carbonization will be insufficient and the effect of transferring oxygen and moisture to the self-heating iron powder will not be achieved.
[0080] 1.2 Preparation process of self-heating iron powder: Self-heating iron powder is made of pure iron powder with a particle size between 50-200 microns, a purity of more than 98wt%, and a specific surface area of 3-4m² / g. The particle size will affect the reaction rate and heat release efficiency of the iron powder. Too large a particle size will reduce the self-heating reaction rate, and too small a particle size may cause agglomeration problems.
[0081] The pure iron powder substrate is treated with NH3 plasma, and amino (-NH2) bonds are formed on the surface of the iron powder substrate through plasma treatment, thereby obtaining self-heating iron powder. The amino (-NH2) bonds on the surface of the self-heating iron powder can improve the surface activity of the iron powder, enhance its ability to bind with oxygen and a small amount of impurity moisture in asphalt, and improve the efficiency of the thermal reaction. The ammonia plasma treatment process is as follows: the iron powder substrate is evenly placed in the plasma treatment chamber, the reaction chamber is evacuated to a vacuum degree between 5 mTorr and 50 mTorr, oxygen and other impurities in the air are removed, high-purity ammonia is introduced into the reaction chamber, and the pressure is adjusted to 5 mTorr to 100 mTorr, and the reaction gas NH3 is introduced, wherein NH3 (reaction gas): N2 (carrier gas) = 10sccm: 300-500sccm, the iron powder substrate is exposed to the ammonia plasma, and the plasma supply rate is controlled at 50-100W. The active nitrogen atoms and hydrogen atoms in the plasma will react with the surface of the iron powder to form amino (-NH2) bonds. By controlling the flow ratio of ammonia (NH3) and nitrogen (N2): NH3 (reaction gas): N2 (carrier gas) = 10sccm: 300-500sccm, the number and distribution of amino (-NH2) bonds formed on the surface of the self-heating iron powder can be effectively controlled, thereby avoiding the slow reaction caused by excessive nitridation and the low NH2 bond content that cannot improve the activity of the iron powder.
[0082] Further, an EVA coating is arranged outside the self-heating iron powder, wherein the VA content in the EVA resin is 40%, and toluene is used as a solvent, and 50g of EVA resin is dissolved in every 1L of toluene to obtain an EVA solution. Using a spray gun device, the EVA solution is evenly sprayed on the surface of the self-heating iron powder. The spraying speed and distance are controlled to ensure that the coating evenly covers the surface of the iron powder, and the spraying thickness is 50 microns to 200 microns. And dried. The iron powder sprayed with the EVA coating after drying is placed in an ultrasonic cleaner, and the high-frequency vibration of ultrasound is used to disperse the iron powder. The ultrasonic treatment time is 5-30 minutes.
[0083] 1.3 Core layer granulation The partially carbonized plant fiber and the self-heating iron powder in the core layer are mixed in proportion, and the mass ratio of the partially carbonized plant fiber and the self-heating iron powder is 1~2.5:1. Add a methyl cellulose solution binder (concentration 1wt%-3wt%) with a mass percentage of 5%-10% of the total material, mix, and use a high-speed stirrer to stir at room temperature for 10 minutes to ensure that the methyl cellulose solution is evenly distributed in the mixture. The mixed material is fed into a granulator and formed into 3-5mm particles by extrusion or roller granulation technology. The temperature is controlled at 60-80°C during the granulation process, and the protective gas is nitrogen.
[0084] Step 2: Coating the middle layer Heat the microcrystalline wax to above its melting point (80°C) to completely melt it. Place the mixed core layer particles in a rotating container and use the dipping method to evenly dip the molten wax into the internal mixture, ensuring that each core layer particle is evenly coated with a layer of wax. Rotate the rotating container at a speed of 150 rpm for 5 minutes to ensure that the coating is evenly distributed. Cool the wax-coated particles naturally at room temperature or use cold air to accelerate cooling to solidify the wax middle layer. Use high-frequency vibration of ultrasound to disperse the particles, and the ultrasonic treatment time is 5 minutes.
[0085] Step 3: Coating the outer covering layer Select EVA resin with a VA content of 40wt% and a melting point of 60-70°C as the molten raw material. Heat EVA to above its melting point (70°C) to make it completely melted. Use a spray gun to evenly spray the EVA melt on the surface of the particles. Control the spraying speed and distance to ensure that the coating evenly covers the surface of the iron powder, and the spraying thickness is 500 microns to 800 microns. And dry it. Use high-frequency vibration of ultrasound to disperse the particles, and the ultrasonic treatment time is 10 minutes.
[0086] Based on common knowledge in the art, the preparation methods of the above-mentioned Examples 2-5 can be used in combination to synergize their beneficial effects.
[0087] In addition, N2 gas protection can be further used in each step of the preparation method to avoid oxidation reaction of the iron powder. Appropriate amounts of dispersants and protective agents can be added when the powder is dispersed. Those skilled in the art are familiar with the basic settings and will not be repeated here.
[0088] Comparative test: This comparative test selected SBS modified asphalt and TPS modified asphalt, which are common in the field, as the test objects. The construction temperature of the above two types of asphalt is relatively high, and the construction is difficult and energy-intensive. The construction temperature in the test refers to the set temperature of the equipment that heats the asphalt to the working temperature. 3wt% of warm mix agent was added to SBS or TPS modified asphalt to measure the change in its construction temperature, thereby detecting the effectiveness of the warm mix agent. The comparative test data is the value obtained by repeating the test 5 times under the same conditions and taking the average value.
[0089] No.: #1——Comparative Example 1: Commercially available Sasobit microcrystalline wax type warm mix No.: #2 - Warm mix prepared in Example 2 No.: #3 - Warm mix prepared in Example 3 No.: #4 - Warm mix prepared in Example 4 No.: #5 - Warm mix prepared in Example 5 Asphalt Type Warm mix number Mixing temperature (Celsius) Compaction temperature (Celsius) SBS modified asphalt Not Joined 180 175 SBS modified asphalt #1 153 144 SBS modified asphalt #2 142 131 SBS modified asphalt #3 140 130 SBS modified asphalt #4 139 132 SBS modified asphalt #5 138 129 TPS modified asphalt Not Joined 193 168 TPS modified asphalt #1 181 172 TPS modified asphalt #2 171 162 TPS modified asphalt #3 170 158 TPS modified asphalt #4 167 157 TPS modified asphalt #5 168 156 It can be seen that the warm mix agent provided in the present application can effectively improve the thermal efficiency of the self-heating material in the warm mix agent and reduce the construction temperature of asphalt.
[0090] The present invention can achieve the following technical effects: 1) Partial carbonization of plant fibers can improve the specific surface area and adsorption performance of plant fibers while maintaining the toughening properties of plant fibers. Partial carbonization of plant fibers can improve the specific surface area and adsorption performance of plant fibers. Partial carbonization of plant fibers can improve the specific surface area and adsorption performance of plant fibers. Partial carbonization of plant fibers can serve as a carrier to help the self-heating iron powder to be evenly distributed in the composite particles, thereby improving the uniformity and efficiency of thermal energy release; partially carbonized plant fibers have good thermal conductivity, which helps to quickly transfer the heat generated by the self-heating iron powder and improve the overall thermal efficiency; partially carbonized plant fibers also have a high specific surface area and rich pore structure, which can effectively absorb oxygen and moisture. When mixed with self-heating iron powder, it can provide the self-heating iron powder with the oxygen and moisture required for the reaction, smoothly promote the oxidation reaction with the self-heating iron powder, and improve thermal efficiency.
[0091] 2) The amino (-NH2) bonds on the surface of the self-heating iron powder can increase the surface activity of the iron powder, enhance its ability to bind with oxygen and a small amount of impurity moisture in asphalt, and improve the efficiency of the thermal reaction.
[0092] 3) Since the melting point of the EVA resin in the outer coating layer (60-70°C) is lower than that of the middle layer, the EVA resin will soften and melt first during the warm mixing process. After the EVA resin melts, a liquid film is formed on the surface of the particles, which reduces the friction between the particles and asphalt, and helps to improve the dispersion and mixing uniformity of the particles in the asphalt.
[0093] 4) When the middle layer is microcrystalline wax, the thermal expansion coefficient of microcrystalline wax is 200-400 × 10⁻ 6 / °C, the thermal expansion coefficient of EVA resin is 50-150 × 10⁻ 6 / °C. During the warm mix process, as the temperature rises, the microcrystalline wax layer will expand more significantly than the EVA resin layer. Due to the large thermal expansion coefficient of microcrystalline wax, its volume growth ratio is greater than that of EVA resin. When the EVA resin melts first, the expansion of the microcrystalline wax layer will generate internal pressure on the EVA liquid film, making the EVA liquid film easier to open. After the EVA liquid film is opened, the porous carbonized coconut shell fiber and self-heating iron powder inside are more likely to flow out and contact with the asphalt substrate, thereby improving the efficiency of the thermal reaction during the warm mix process.
[0094] The above describes the embodiments of the present invention in detail. However, the present invention is not limited to the above embodiments, and various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. An organic viscosity-reducing warm-mix agent for water conservancy projects, characterized in that: It is composed of a core layer, an intermediate layer and an outer coating layer from the inside to the outside, wherein the inner core layer includes a mixture of partially carbonized plant fibers and self-heating iron powder, the intermediate layer includes a viscosity-reducing material, and the outer coating layer includes an EVA layer; the melting point of the intermediate layer is higher than that of the outer coating layer; the mass ratio of the partially carbonized plant fibers to the self-heating iron powder is 1~2.5:1; the base material of the self-heating iron powder is selected to have a particle size between 50-200 microns, a purity of more than 98wt%, and a specific surface area between 3-4m² / g; the length of the plant fiber is 2-5mm.
2. The organic viscosity-reducing warm-mix agent for water conservancy projects according to claim 1, characterized in that: The partially carbonized plant fiber is a core part of the plant fiber formed by a carbonization reaction, in which at least a portion of the surface is carbonized and a portion of the original plant fiber is retained.
3. The organic viscosity-reducing warm-mix agent for water conservancy projects according to claim 1, characterized in that: Viscosity reducing materials include aromatic hydrocarbons.
4. The organic viscosity-reducing warm-mix agent for water conservancy projects according to claim 3, characterized in that: The aromatic hydrocarbon is naphthalene.
5. The organic viscosity-reducing warm-mix agent for water conservancy projects according to claim 4, characterized in that: The viscosity-reducing material comprises naphthalene particles dispersed in a paraffin matrix, and the mass percentage of the naphthalene particles is between 60-70%.
6. The organic viscosity-reducing warm-mix agent for water conservancy projects according to claim 1, characterized in that: The VA content of the EVA layer is 40wt% and the melting point is 60-70°C.
7. A method for preparing the organic viscosity-reducing warm-mix agent for water conservancy projects as claimed in any one of claims 1 to 6, characterized in that: The method comprises: preparing a core layer, coating an intermediate layer, and coating an outer coating layer.
Citation Information
Patent Citations
A self-heating warm-mix asphalt repair material and its construction method
CN111892336B
Self-heating double-component emulsified asphalt coating as well as preparation method and use method thereof
CN114149747A